Female hydrocele (Health Renaissance, 2011)
The processus vaginalis is an envagination of parietal peritoneum which accompanies the round ligament through the inguinal ring into the inguinal canal. The portion of processus vaginalis within the inguinal canal in women is called ‘the canal of Nuck’. When the processus vaginalis fails to close, it can result in a hernia or hydrocele in both men and women. Female hydrocele of the canal of Nuck is uncommon. A literature search revealed that little has been published on this condition. We present a case of a hydrocele of the canal of Nuck in a 23-year old female who had an irreducible swelling over the left groin for three months and increasing in size on straining. The cyst was excised with round ligament and a repair of inguinal canal with closure of deep ring was done. Keywords: hydrocele; female hydrocele; canal of Nuck DOI: http://dx.doi.org/10.3126/hren.v9i2.4985 Health Renaissance 2011: Vol.9 (No.2): 116-118